2009
DOI: 10.1371/journal.pone.0007598
|View full text |Cite
|
Sign up to set email alerts
|

COP9 Limits Dendritic Branching via Cullin3-Dependent Degradation of the Actin-Crosslinking BTB-Domain Protein Kelch

Abstract: Components of the COP9 signalosome (CSN), a key member of the conserved 26S proteasome degradation pathway, have been detected to be altered in patients of several debilitating syndromes. These findings suggest that CSN acts in neural circuits, but the exact function of CSN in brain remains unidentified. Previously, using Drosophila peripheral nervous system (PNS) as a model system, we determined that CSN is a critical regulator of dendritic morphogenesis. We found that defects in CSN led to the strikingly con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 64 publications
1
24
0
Order By: Relevance
“…Here we provided evidence that inc induction or Cul3-RNAi knockdown during development, but not exclusively during adulthood, could rescue (in the case of induction) or phenocopy (in the case of knockdown) their respective mutant/RNAi phenotypes. The Cul3 results are consistent with an established role for Cul3 in dendritic and axonal arborization, in which dendritic and axonal arborization are reduced in Cul3 mutants [29], [40]. Our data also revealed a stochastic branching defect in MB neurons in 26% of inc mutants, in which they lack a single α- or β-lobe.…”
Section: Discussionsupporting
confidence: 89%
“…Here we provided evidence that inc induction or Cul3-RNAi knockdown during development, but not exclusively during adulthood, could rescue (in the case of induction) or phenocopy (in the case of knockdown) their respective mutant/RNAi phenotypes. The Cul3 results are consistent with an established role for Cul3 in dendritic and axonal arborization, in which dendritic and axonal arborization are reduced in Cul3 mutants [29], [40]. Our data also revealed a stochastic branching defect in MB neurons in 26% of inc mutants, in which they lack a single α- or β-lobe.…”
Section: Discussionsupporting
confidence: 89%
“…Three putative actinbinding and depolymerizing enzymes were found that are unique to D. noxia saliva and may play a role in preventing or resolving phloem obstructions. Kelch-like protein, most abundant in RWA5, was found to promote actin disassembly and rearrangement in Drosophila melanogaster [82,83]. Cofilin/ actin depolymerizing factor, observed only in RWA5, is an actin depolymerizing factor found in both plants and insects and is involved in actin depolymerization, signaling, and Golgi-mediated secretion [84,85].…”
Section: 6mentioning
confidence: 99%
“…Loss of Cul1 or of the F-box protein Slimb represses arborization, while loss of Cul3 enhances it, suggesting that the Cul1 and Cul3 E3 complexes target proteins with markedly different roles in dendritogenesis. One of the proposed targets for the Cul3 complex is Kelch, an actin cross-linking protein [76]. Mutation of Cul3 increases levels of Kelch protein, while mutation of Kelch reduces dendritic arborization and represses the Cul3 increased arborization phenotype [76], further establishing the complex link between the proteasome and the cytoskeleton.…”
Section: Dendritic Morphogenesis and Arborization By The Upsmentioning
confidence: 99%